2000
DOI: 10.1007/s004390000367
|View full text |Cite
|
Sign up to set email alerts
|

Genetic screening of the lipoprotein lipase gene for mutations associated with high triglyceride/low HDL-cholesterol levels

Abstract: The lipoprotein lipase (LPL) enzyme plays a major role in lipid metabolism, primarily by regulating the catabolism of triglyceride (TG)-rich lipoprotein particles. The gene for LPL is an important candidate for affecting the risk of atherlosclerosis in the general population. Previously, we have shown that the HindIII polymorphism in intron 8 of the LPL gene is associated with plasma TG and HDL-cholesterol variation in Hispanics and non-Hispanic whites (NHWs). However, this polymorphism is located in an intron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 59 publications
9
54
0
1
Order By: Relevance
“…Other identified SNPs in the ApoC3 (À482, À2854), ApoA5 (À3, 56, IVS3 þ 476,1259) and LPL (N291S, D9N, V108v, HindIII) genes have been shown to influence lipid metabolism and/ or cardiovascular risk outcomes in some studies. 7,[21][22][23][24] Furthermore, other genes such as the ApoE, ApoA1, ApoB, hepatic lipase and PPAR genes have been investigated for their association with lipid levels and/or cardiovascular disease outcomes. 4,10,[25][26][27] Since weight gain and BMI are significantly correlated with serum triglycerides and cholesterol levels, it is possible that genetic variants which may influence the extent of weight gain during treatment with antipsychotics, such as the polymorphisms in the 5-HT2C receptor (À759 T/C), 28,29 polymorphisms of the leptin gene, 28,30 and polymorphisms in the a2A receptor (À1291 C/G) 31 may also be related to deferential drug  gene effects on serum lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Other identified SNPs in the ApoC3 (À482, À2854), ApoA5 (À3, 56, IVS3 þ 476,1259) and LPL (N291S, D9N, V108v, HindIII) genes have been shown to influence lipid metabolism and/ or cardiovascular risk outcomes in some studies. 7,[21][22][23][24] Furthermore, other genes such as the ApoE, ApoA1, ApoB, hepatic lipase and PPAR genes have been investigated for their association with lipid levels and/or cardiovascular disease outcomes. 4,10,[25][26][27] Since weight gain and BMI are significantly correlated with serum triglycerides and cholesterol levels, it is possible that genetic variants which may influence the extent of weight gain during treatment with antipsychotics, such as the polymorphisms in the 5-HT2C receptor (À759 T/C), 28,29 polymorphisms of the leptin gene, 28,30 and polymorphisms in the a2A receptor (À1291 C/G) 31 may also be related to deferential drug  gene effects on serum lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Since the HindIII polymorphism is located in the middle of intron 8, it is not considered to be functional but rather in linkage disequilibrium with a putative functional variant. Some groups, including ours, have attempted to find such a functional variant and identified coding SNPs, including D9N, N291S and S447X [6,[19][20][21]. Among these, only the S447X was common with a frequency of about 9% in Caucasians.…”
Section: Introductionmentioning
confidence: 98%
“…Several common LPL genetic variants have been widely studied, and among them HindIII in intron 8 (T→G at position 481), and S447X in exon 9 are of particular interest because of their common occurrence (25% and 9% of the less common alleles, respectively in most populations) and their associations with plasma lipid profile [6][7][8][9][10][11] and susceptibility to CAD [10][11][12][13][14][15] in several studies, although some inconsistent results have also been reported [16][17][18]. Since the HindIII polymorphism is located in the middle of intron 8, it is not considered to be functional but rather in linkage disequilibrium with a putative functional variant.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that there may be common underlying genetic determinants between BP regulation and lipid metabolism. Human lipoprotein lipase (LPL) plays a major role in the determination of the plasma lipid and lipoprotein profile, and is a ratelimiting enzyme responsible for the hydrolysis of triglycerides (TG) in chylomicrons (CM) and very-low-density lipoprotein (VLDL) (3). The LPL gene may be one of these genetic determinants.…”
Section: Introductionmentioning
confidence: 99%